Task design principles in Socioepistemology - Hinojos Ramos, Jesús Eduardo; Romero Fonseca, Fabián Wilfrido; Farfán Márquez, Rosa María (IE Revista de Investigación Educativa de la REDIECH, 2020)
A position about the principles of task design in Educational Mathematics from Socio-epistemology is proposed, taking as a premise the reflection done from diverse research groups regarding how task-designs for research and school intervention are justified and carried out. We make an articulation between the design principles in intermediate level and domain-specific frames with the principles of the Socioepistemological Theory and the problematization of the mathematical knowledge. In addition, two examples of research within this theoretical framework are shown, one focused on the Fourier series in its context of origin and another one in electrical engineering as a referral practice for the resignification of the steady-state, both examples help to illustrate how task-design principles give foundation to the learning situations of both research projects. We conclude that the problematization of the mathematical knowledge plays an important role on the construction of design principles, as the problematization proposes re-designs for the school mathematics discourse.